LiTaO3 phonon dispersion and ferroelectric transition calculated from first principles - Friedrich, Michael; Schindlmayr, Arno; Schmidt, Wolf Gero; Sanna, Simone (Physica Status Solidi B)
The phonon dispersions of the ferro‐ and paraelectric phase of LiTaO3 are calculated within density‐functional perturbation theory. The longitudinal optical phonon modes are theoretically derived and compared with available experimental data. Our results confirm the recent phonon assignment proposed by Margueron et al. [J. Appl. Phys. 111, 104105 (2012)] on the basis of spectroscopical studies. A comparison with the phonon band structure of the related material LiNbO3 shows minor differences that can be traced to the atomic‐mass difference between Ta and Nb. The presence of phonons with imaginary frequencies for the paraelectric phase suggests that it does not correspond to a minimum energy structure, and is compatible with an order‐disorder type phase transition.

Simulation of the ultrafast nonlinear optical response of metal slabs - Wand, Mathias; Schindlmayr, Arno; Meier, Torsten; Förstner, Jens (Physica Status Solidi B)
We present a nonequilibrium ab initio method for calculating nonlinear and nonlocal optical effects in metallic slabs with a thickness of several nanometers. The numerical analysis is based on the full solution of the time‐dependent Kohn–Sham equations for a jellium system and allows to study the optical response of metal electrons subject to arbitrarily shaped intense light pulses. We find a strong localization of the generated second‐harmonic current in the surface regions of the slabs.
Keywords: tet_topic_shg

Quasiparticle calculations for point defects on semiconductor surfaces - Hedström, Magnus; Schindlmayr, Arno; Scheffler, Matthias (Physica Status Solidi B)
We discuss the implementation of quasiparticle calculations for point defects on semiconductor surfaces and, as a specific example, present an ab initio study of the electronic structure of the As vacancy in the +1 charge state on the GaAs(110) surface. The structural properties are calculated with the plane‐wave pseudopotential method, and the quasiparticle energies are obtained from Hedin's GW approximation. Our calculations show that the 1a″ vacancy state in the band gap is shifted from 0.06 to 0.65 eV above the valence‐band maximum after the self‐energy correction to the Kohn‐Sham eigenvalues. The GW result is in close agreement with a recent surface photovoltage imaging measurement.